The Impact of Green accounting, CSR Disclosure and Capital Structure on Financial Performance - Julita Fransiska; Inten Meutia; Emylia Yuniarti (Politeknik Ganesha Medan, 2026)
This study aims to analyze the effect of green accounting, CSR disclosure, and capital structure on financial performance, with firm size as a control variable, in consumer sector companies listed on the Indonesia Stock Exchange during the 2021 to 2024 period. This study uses a quantitative approach with a purposive sampling method and generates 276 observations. The data used are secondary data obtained from annual financial reports and sustainability reports. Data analysis was conducted using panel data regression with EViews 12. The results show that green accounting, CSR disclosure and capital structure through debt to asset ratio have an effect on financial performance. These findings indicate that environmental cost management, CSR Disclosure and financing structure play an important role in supporting corporate financial performance. On the other hand, capital structure through long term debt ratio has no effect on financial performance, indicating that long term devt ratio has not been able to make a significant contribution to the financial performance of consumer sector companies. Firm size, as a control variable, also has effect on financial performance, indicating that company size is a determining factor of financial performance. This study provides an empirical contribution by integrating green accounting, CSR disclosure, and capital structure into a single analytical model to explain the financial performance of consumer sector companies in Indonesia.